An improved method of MgFe-layered double hydroxide/ biochar composite synthesis. (20th March 2023) - Bian, Haohao; Shen, Cheng; Liu, Wanpeng; Man, Yu Bon; Wong, Ming Hung; Christie, Peter; Shan, Shengdao; Wang, Minyan; Zhang, Jin
Abstract: Layered double hydroxides (LDHs) and their composites are a promising platform for a wide range of applications, especially in the environmental field. However, the facile and efficient synthesis of high-quality LDHs and their composites remains a challenge. Here, an improved co-pyrolysis method has been developed to synthesize LDH/biochar composites. A composite material was prepared by directly anchoring MgFe-LDH on corn stover by co-precipitation with FeCl3 and Mg(OH)2, and then through pyrolysis. The main features of this improved method are the use of the solubility product Mg(OH)2 to maintain the pH of the mixture at ∼10 (the optimum for LDH precipitation), eliminating the cumbersome pH control steps of the traditional co-precipitation method, and the low rate of solid-liquid reaction to obtain high LDH crystallinity and purity. This produces improved properties of the MgFe-LDH/biochar composite after pyrolysis: higher loading of MgFe-LDH, larger specific surface area of the composite, a more stable layered structure, and a more customizable LDH. The theoretical maximum adsorption capacity of phosphorus for the composite was 379.4 mg L −1 according to an adsorption isotherm study, and the dominant adsorption mechanism is chemical adsorption accompanied by physical adsorption. In actual wastewater applications, >80% of total phosphorus in biogas slurry was removed via adsorption, indicating that the composite is highly efficient in phosphorus selectivity in wastewaters with complex components. Here, a more sustainable synthesis method of LDH/biochar composite has been developed with high application potential. Graphical abstract: Image 1 Highlights: A facile innovative method for the synthesis of MgFe-LDH/biochar composites is proposed. Mg(OH)2 was used to spontaneously adjust the co-precipitation pH. MgFe-LDH anchored on biomass using the new method has higher crystallinity and purity. The derived MgFe-LDH/biochar exhibits an excellent phosphorus removal capability.